DOI: 10.14264/uql.2015.687
|View full text |Cite
|
Sign up to set email alerts
|

The free-living Symbiodinium reservoir and scleractinian coral symbiont acquisition

Abstract: The genus Symbiodinium (Dinophyceae, Suessiales), a group of geographically widespread marine dinoflagellates, comprises numerous ecologically and genetically distinct taxa. Symbiodinium spp.establish intracellular symbioses with cnidarians, infecting hosts such as jellyfish, sea anemones, octocorals and reef-building corals. The energetic demands of hosts can be met at varying levels by Symbiodinium through translocation of photosynthetically-fixed carbon, assisting in the formation of coral reefs. The cnidar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 204 publications
(429 reference statements)
1
4
0
Order By: Relevance
“…However, we view www.nature.com/scientificreports www.nature.com/scientificreports/ thousands of kilometers away may be limited 63,64 . This idea is supported by previous research demonstrating that Symbiodiniaceae tend to disperse locally 65,66 and endosymbiotic Symbiodiniaceae are competent in the water column for only approximately seven days 67 , while coral larval competency can be one month or more [68][69][70] .…”
Section: Discussionsupporting
confidence: 71%
“…However, we view www.nature.com/scientificreports www.nature.com/scientificreports/ thousands of kilometers away may be limited 63,64 . This idea is supported by previous research demonstrating that Symbiodiniaceae tend to disperse locally 65,66 and endosymbiotic Symbiodiniaceae are competent in the water column for only approximately seven days 67 , while coral larval competency can be one month or more [68][69][70] .…”
Section: Discussionsupporting
confidence: 71%
“…When viewed from a symbiont-centric perspective, one can posit Symbiodinium employs a strategy of pathogen-like shedding, wherein cells actively released from current hosts are not related to density regulation but rather a means to reach new habitats, or in this case, additional host individuals capable of establishing a symbiosis (reviewed by Holt & Barfield 2006). Under this hypothesis, it is improbable that released cells need to be indefinitely free-living, which is consistent with longevity estimates for Symbiodinium of~7 days in the environment (Nitschke 2015). Instead, Symbiodinium sources are continually renewed and survival of individual cells is likely diminished due to decreased habitat suitability, increased uncertainty and limited access to nutrients.…”
Section: Free-living Symbiodiniummentioning
confidence: 74%
“…Biogeographical and ecological studies have shown that the center of Symbiodiniaceae diversity overlaps with the “Coral Triangle” (LaJeunesse et al, 2012), which is close to the IR and LR and far away from the HC and HR. The physiological evidence suggests that Symbiodiniaceae swim just 3–10 m over the course of one day (Fitt and Trench, 1983), and have a lifespan of approximately seven days in their natural environment (Nitschke, 2015). They are most likely dependent on sea currents for dispersal (Wirshing et al, 2013; Thornhill et al, 2017).…”
Section: Discussionmentioning
confidence: 99%